P-025 Calcium Channel Blocker Infusion Improves Vessel Measurement Accuracy and Aneurysm Occlusion Following Flow Diversion. (29th July 2016) - Alexander, M; Darflinger, R; Settecase, F; Nicholson, A; Cooke, D; Amans, M; Hetts, S; Dowd, C; Higashida, R; Halbach, V
Abstract : Introduction/purpose: To best achieve complete occlusion of aneurysms treated with flow diverters (FDs), devices must be accurately sized to precisely match the parent vessel diameter. Appropriately sized FDs will have maximal coverage over the aneurysm neck and will be more likely to induce thrombosis. Catheterization for diagnostic angiography can cause vasospasm that may affect vessel measurements. This study evaluates the effects of intra-arterial infusion of a calcium channel blocker (CCB) on angiographic measurements in patients treated with FDs, investigating the impact on the final diameter of the expanded stent following deployment and subsequent occlusion. Materials and methods: Retrospective analysis was performed of prospectively maintained procedure records to identify patients with aneurysms treated with FDs. In all patients, pre-treatment measurements were recorded for vessel diameter of the distal and proximal landing zones, as well as maximum and minimum diameters between these segments. Post-treatment measurements of the stent itself following deployment were recorded at the distal and proximal ends in addition to maximum and minimum diameters. When CCB was infused prior to treatment, post-infusion pre-treatment measurements were recorded. All measurements were performed after calibrating to a catheter included on the image. Rates of occlusion and time to confirmed occlusion were noted for all patients. Independent-sample 2 tailed T-tests were performed to assess for differences in pre- and post-treatment measurements, rates of occlusion, and time to confirmed occlusion between groups with and without CCB infusion. Results: 21 FDs were deployed to treat 19 aneurysms in 18 patients. CCB infusion was performed prior to deployment of 9 devices. The change in measurements noted after CCB infusion are summarized in Table 1 . No significant difference was noted between groups for pre- and post-treatment measurement changes. Subsequent aneurysm occlusion was more likely to occur in the CCB infusion group (100% vs. 44.4%, p < 0.001). No significant difference was noted between groups for time to occlusion (313.7 vs. 392.8 days, p = 0.807) or overall angiographic follow up time (209.1 vs. 302.5 days, p = 0.326). Conclusion: Optimization of device sizing is important to increase FD density over the aneurysm neck and promote thrombosis. To improve accuracy of measurements of parent vessels prior to device selection, CCB infusion can reduce the effects of mild vasospasm. In this study, subsequent aneurysm occlusion was more likely to occur following FD treatment when device size selection was based on measurements performed following CCB infusion. Disclosures: M. Alexander: None. R. Darflinger: None. F. Settecase: None. A. Nicholson: None. D. Cooke: None. M. Amans: None. S. Hetts: None. C. Dowd: None. R. Higashida: None. V. Halbach: None.